Risk Perception Towards COVID-19 and Its Associated Factors Among Waiters in Selected Towns of Southwest Ethiopia - Asefa A; Qanche Q; Hailemariam S; Dhuguma T; Nigussie T (Dove Medical Press, 2020)
Adane Asefa,1 Qaro Qanche,1 Shewangizaw Hailemariam,2 Tadesse Dhuguma,3 Tadesse Nigussie1 1Department of Public Health, College of Health Science, Mizan-Tepi University, Mizan Aman, Ethiopia; 2Department of Midwifery, College of Health Science, Mizan-Tepi University, Mizan Aman, Ethiopia; 3Department of Medical Laboratory, College of Health Science, Mizan-Tepi University, Mizan Aman, EthiopiaCorrespondence: Adane AsefaDepartment of Public Health, College of Health Science, Mizan -Tepi University, Mizan-Aman, EthiopiaEmail adane779@gmail.comBackground: Waiters working in hotels, pensions, restaurants, and cafeteria are more susceptible to COVID-19 and easily transmit the virus to others because they interact with almost all individuals who enter those establishments. However, information regarding their risk perception is scarce; hence, this study aimed to assess risk perception regarding COVID-19 and its associated factors among waiters working in the selected towns of southwest Ethiopia.Methods: A cross-sectional study was conducted from June 1 to 15, 2020. The interview-administered structured questionnaire was used to collect data. Data were entered into Epi data manager version 4.0.2 and exported to SPSS version 24 for analysis. Multiple linear regression analysis was done to identify factors associated with risk perception. A p-value of less than 0.05 was used as a level of significance.Results: A total of 416 waiters were interviewed, with a 98.6% response rate. The mean age of respondents was 27.26 (SD=8.35) years. More than half (53.4%) agreed that COVID-19 causes more deaths than other respiratory diseases. Regarding overall risk perception, two hundred twenty-two (53.4%) participants had high-risk perceptions concerning COVID-19. Risk perception was associated with age (β= 0.10; 95% CI: 0.02, 0.18), knowledge of COVID-19 (β=0.50, 95% CI: 0.23, 0.76) and preventive behaviors (β=0.62; 95% CI: 0.33, 0.90).Conclusion: A higher level of risk perception was found regarding the COVID-19. Proper risk communication to promote protective behaviors is very essential since waiters are more at risk to be infected with COVID-19 and their infection with the virus has important public health implications.Keywords: risk perception, COVID-19, coronavirus, waiters